RELATWE ABUNDANCE AND MEL VARIATION OF ZOOPLANKTON FROM SOUTH WEST COAST OF INDIA - SANTHAKUMARI, V.; PETER, K. I. (Journal of Indian Fisheries Association, 2015)
Relative abundance and diurnal variations of zooplankton from six anchor stations alongKerala coast, were investigated. Samples were collected during April - May 1988 at three hourintervals from depths varying between 15 m and 40 tn from the traditional fishing grounds ofKerala coast. Average biomass values ranged from 45-95 ml 100/m -3. Increase in zooplardttonat night was discernible at most of the stations and the highest biomass noticed was 131 ml 100/m"3. Copepods formed the most abundant group, of which calanoids predominated. A swarmof the hydromedusan species, Aequorea conica, (181/m-3) was seen at night. Quantitative andqualitative variations of various zooplankton groups from six stations in relation to selectedphysico chemical factors are discussed. Maxium fish larvae was observed in the night samples.Relatively high abundence of sardines, carangids and flat fish larvae in the collections is inagreement with the predominance of fish catch from the area of study.